THE EFFECT OF ETHANOL EXTRACT OF ZIZIPHUS MAURITIANA LAM. LEAF ON ALLOXAN-INDUCED RAT - Tcanty Indrianti; Ali Napiah Nasution; Evelyn Angie; Clarissa Lister; Veranyca Chiuman (The Islamic Education and Multiculturalism Foundation, 2024)
Bidara (Ziziphus mauritiana Lam.) or Indian jujube or ber is one Indonesian endemic plant which widely used as a traditional remedy in Indonesia and other Asian countries. Bidara leaves are commonly used as a remedy for diarrhea, liver diseases, and diabetes. This study aims to determine the effect of ethanol extract of bidara leaves (Z. mauritiana Lam.) on alloxan-induced male Wistar strain rat’s (Rattus norvegicus) liver. This is an experimental study with a randomized pretest-posttest with a control group design. This study involved 24 male Wistar strain rats (R. norvegicus) which were divided into 6 separate groups induced with alloxan and each group received a different intervention accordingly. Data in this study shows that ethanol extract of bidara leaves contains alkaloids, saponins, flavonoids, and glycoside compounds. This study also found that ethanol extract of bidara leaves at doses as low as 150 mg/kgBW managed to decrease the blood glucose, SGOT, and SGPT levels better than negative control and as effective as metformin. Escalation of SOD activity was also found to be directly proportional to dose increase, however, the highest concentration of MDA was also found in the highest dose of ethanol extract of bidara leaves. It can be concluded that ethanol extract from bidara leaves has anti-hyperglycemic (p<0.001) and hepatoprotective (p<0.05) effects, but the antioxidant properties cannot be determined according to this study’s data.